Ultrasound Evaluation of Left Ventricular Function in Coronary Artery Ectasia The Added Value of 2D Speckle-tracking Echocardiography - Elshaer, Osama A (Journal of the Saudi Heart Association, 2025)
© 2025 Saudi Heart Association.